Karakteristik Tafsir al-Jawâhir al-Hisân fî Tafsîr al-Qur`ân al-Karîm Karya Imam al-Tsa’alibi - Mhd. Idris (IAIN Bengkulu, 2022)
This study discusses the characteristics of the book of interpretation of al-Jawâhir al-Hisân Fî Tafsîr al-Qur`ân al-Karîm by Imam al-Tsa'alibi. For this reason, this study aims to find out about the general profile of the author of the book, the background of writing, the method and style of interpretation, and the feature it has. This research is descriptive-analytical literature research. The primary source used is the book of Tafsir al-Tsa'alibi with the title al-Jawâhir al-Hisân Fî Tafsr Al-Qur`ânil Karîm and literature related to this discussion as secondary sources. The results showed that the book of Tafsir al-Jawâhir al-Hisân was the work of Abu Zaid, Abdurrahman bin Muhammad bin Makhluf al-Tsa'alibi, al-Jaza'iri, al-Maliki. Born in 786 H and died in 875 H. This interpretation uses the tahlili method and does not have a special feature that stands out, because all aspects and problem areas are well discussed and relatively balanced in interpretation. In addition, the specialty of this book also lies in systematic writing which is easy to read and understand because it is systematically arranged in a language that is not difficult and suitable for consumption by many people.